A Comparison of the GlideScope Video Laryngoscope to the C-MAC Video Laryngoscope for Intubation in the Emergency Department - Mosier, Jarrod (Ann Emerg Med, 2013)
STUDY OBJECTIVE: There is growing use of video laryngoscopy in US emergency departments (EDs). This study seeks to compare intubation success between the GlideScope video laryngoscope and the C-MAC video laryngoscope (C-MAC) in ED intubations. METHODS: This was an analysis of quality improvement data collected during a 3-year period in an academic ED. After each intubation, the operator completed a standardized data form reporting patient demographics, indication for intubation, device(s) used, reason for device selection, difficult airway characteristics, number of attempts, and outcome of each attempt. An attempt was defined as insertion of the device into the mouth regardless of attempt at tube placement. The primary outcomes were first pass and overall intubation success. The study compared success rates between the GlideScope video laryngoscope and the C-MAC groups, using multivariable logistic regression and adjusting for potential confounders. RESULTS: During the 3-year study period, there were 463 intubations, including 230 with the GlideScope video laryngoscope as the initial device and 233 with the C-MAC as the initial device. The GlideScope video laryngoscope resulted in first-pass success in 189 of 230 intubations (82.2%; 95% confidence interval [CI] 76.6% to 86.9%) and overall success in 221 of 230 intubations (96.1%; 95% CI 92.7% to 98.2%). The C-MAC resulted in first-pass success in 196 of 233 intubations (84.1%; 95% CI 78.8% to 88.6%) and overall success in 225 of 233 intubations (96.6%; 95% CI 93.4% to 98.5%). In a multivariate logistic regression analysis, the type of video laryngoscopic device was not associated with first-pass (odds ratio 1.1; 95% CI 0.6 to 2.1) or overall success (odds ratio 1.2; 95% CI 0.5 to 3.1). CONCLUSION: In this study of video laryngoscopy in the ED, the GlideScope video laryngoscope and the C-MAC were associated with similar rates of intubation success.